2020
DOI: 10.4314/ejhs.v30i3.2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Patient Safety Climate and Medical Error Reporting Rate among Iranian Hospitals Using a Structural Equation Modeling

Abstract: BACKGROUND: Improving patient safety is a global health imperative, and patient safety climate is one of the components one that plays an important role in promoting patient safety. Medical error reporting is a way through which it can be evaluated and prevented in the future. The aim of this study was to assess the relationship between patient safety climate and medical error reporting in military and civilian hospitals.METHODS: This research was conducted by using structural equation modeling in the selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Also, considering the significant relationship that was found between patients' ethical climate and most of the components of nursing error reporting, hospital managers must develop appropriate programmes to promote health literacy and patient awareness in terms of disease recognition, self-care principles, and care-treatment methods and also provide the necessary conditions for further disclosure of nursing errors by improving patients' awareness of the errors that occurred and the measures taken after the error occurrence. colleagues in Kerman showed no significant relationship between the rate of error reporting by nurses and the patient's safety climate (Shahabinejad et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, considering the significant relationship that was found between patients' ethical climate and most of the components of nursing error reporting, hospital managers must develop appropriate programmes to promote health literacy and patient awareness in terms of disease recognition, self-care principles, and care-treatment methods and also provide the necessary conditions for further disclosure of nursing errors by improving patients' awareness of the errors that occurred and the measures taken after the error occurrence. colleagues in Kerman showed no significant relationship between the rate of error reporting by nurses and the patient's safety climate (Shahabinejad et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Nursing managers, through patient independence in clinical decision‐making and implementation of patient‐centred care, can improve the ethical climate of patients and consequently, increase the trust between nurses and patients. A study by Shahabinejad and colleagues in Kerman showed no significant relationship between the rate of error reporting by nurses and the patient's safety climate (Shahabinejad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to create a culture in which health professionals are encouraged and supported to identify and report AEs without fear of punitive action or blame. Reporting of AEs is an essential component of effective strategies to improve patient safety that includes identification of error, reporting, analysis and corrective actions ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shahabinejad et al confirmed this outcome. 35 Gyekye and Salminen found weak gender-safety connections. 36 As most of the current sample were female nurses, they should assess the hospital's safety climate positively, according to Lin et al 37 The 'younger age group' got the lowest score, contrary to Holden et al, 38 who observed substantial variations between age group and safety climate ratings.…”
Section: Associations Among Nurses' Authentic Leadership and Safety C...mentioning
confidence: 99%